Administration of Lactobacillus fermentum KBL375 Causes Taxonomic and Functional Changes in Gut Microbiota Leading to Improvement of Atopic Dermatitis - Kim, Woon-Ki; Jang, You Jin; Han, Dae Hee; Seo, Boram; Park, SungJun; Lee, Chang Hyung; Ko, GwangPyo (Frontiers in Molecular Biosciences, 2019)
Gut microbiota play an important role in immune responses and energy metabolism. In this study, we evaluated whether administration of Lactobacillus fermentum (L. fermentum) KBL375 isolated from healthy Korean feces improves the atopic dermatitis using the house dust mite (Dermatophagoides farinae)-induced atopic dermatitis (AD) mouse model. Administration of L. fermentum KBL375 significantly decreased dermatitis score, ear and dorsal thickness, and serum immunoglobulin E level in AD-induced mice. Significant reductions in mast cells and eosinophils were discovered in skin tissues from L. fermentum KBL375-treated mice. T helper 2 cell-related cytokines interleukin (IL)-4, IL-5, IL-13 and IL-31 significantly decreased, and anti-inflammatory cytokine IL-10 or transforming growth factor-β increased in skin tissues from L. fermentum KBL375-treated mice. In addition to phenotypic changes in skin tissues, L. fermentum KBL375 treatment induced an increase in the CD4+CD25+Foxp3+ cell population in mesenteric lymph nodes. Taxonomic and functional analyses of gut microbiota showed significantly higher cecum bacterial diversities and abundances including genus Bilophila, Dorea, and Dehalobacterium in L. fermentum KBL375-treated mice. Metabolic analysis of the cecum also showed significant changes in the levels of various amino acids including methionine, phenylalanine, serine, and tyrosine, as well as short chain fatty acids such as acetate, butyrate, and propionate in AD-induced mice due to L. fermentum KBL375 treatment. These altered metabolites in AD-induced mice returned to the levels similar to those in control mice when treated with L. fermentum KBL375. Therefore, L. fermentum KBL375 could be useful for AD treatment by modulating the immune system and inducing various metabolites.